Method for catalytic conversion of carbon dioxide gas into nanographite
Patent Information
- Application Number
- CN202410576523.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-10
AI Technical Summary
[0005]为了解决纳米石墨生产周期长、制备能耗高、石墨化温度高、对生产设备要求严格、催化剂难再生且产物不易分离的问题,本发明的目的是在于提供一种简易、低成本、持续稳定的制备高品质纳米石墨的方法,该方法以二氧化碳为碳源,不但成本低而且可以实现固碳,且过程简单、周期短、能耗低、对设备要求低,容易实现批量化生产
[0024] 1) The process for preparing nano-graphite in this invention is simple, has a short cycle, low energy consumption, low equipment requirements, and is easy to mass-produce.
Smart Images

Figure CN118515268B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing nano-graphite, and more particularly to a method for catalytically converting carbon dioxide gas into nano-graphite, belonging to the field of nano-graphite preparation technology. Background Technology
[0002] Nanographite is a multilayered, sheet-like carbon material with a particle size between 1 and 100 nm. It not only possesses the advantages of ordinary graphite, such as strong lubricity, high electrical conductivity, thermal shock resistance, high temperature resistance (>3800℃), and corrosion resistance, but also exhibits the size effect characteristics of nanoparticles, thus attracting significant attention from researchers in recent years. Currently, nanographite demonstrates enormous application value in materials preparation (high-strength composite materials, conductive / thermal materials, etc.), energy storage (batteries, supercapacitors, etc.), environmental protection (adsorbents, catalysts, etc.), and biomedicine (biosensors, drug delivery, etc.).
[0003] Nanographite can be mass-produced from natural graphite ore through processes such as beneficiation, acid washing / alkali roasting, chemical intercalation, and physical pulverization (e.g., Chinese patents CN111137883A and CN110980721A). However, these methods involve long production cycles, high energy consumption, and significant pollution, resulting in very high prices for this type of nanographite product. High-temperature graphitization (2200–3000℃) of amorphous carbon is currently the mainstream method for producing nanographite (e.g., Chinese patents CN103435032A and CN106498468A). However, it is only effective for soft carbon that is easily graphitized, and the use of graphitization furnaces makes this process very time-consuming and energy-intensive. Catalytic graphitization is a rapidly developing method in recent years that utilizes metal catalysts to convert amorphous carbon into nano-graphite at 1000–1500℃ (e.g., Chinese patents CN106495147A and CN116040622A). However, it requires a very cumbersome impurity removal process to address the catalyst residue problem. Chinese patent CN103510103A discloses a method that converts amorphous carbon into nano-graphite without a catalyst, using a three-stage electrode system in a molten salt electrolyte at 700–1000℃. However, the nano-graphite products produced by this method contain a large number of electrolytic impurities, which are difficult to remove through washing, resulting in disordered accumulation of nano-graphite flakes with a lateral size of micrometers.
[0004] Recently, using carbon dioxide, a major greenhouse gas, to replace natural graphite or amorphous carbon in the preparation of nanographite has become a research hotspot. Chinese patent CN106744914A discloses a method for preparing nanographite sheets, which utilizes a gas-solid reaction between CaC2 powder and pure CO2 gas at 600–900℃, followed by washing with hydrochloric acid and distilled water to remove the byproduct CaO, thus obtaining nanographite. This method is simple and effective, but it requires simultaneous heating and pressurization; that is, it needs to maintain a CO2 gas pressure of 0.1–5 MPa continuously at 600–900℃ after vacuuming to achieve the nano-sizing process, which places very high demands on the reaction equipment. Chinese patent CN109354012A discloses a low-cost, large-scale graphene preparation method, which involves passing CO2 gas into a semi-solid or liquid magnesium alloy at 550–750℃, using a magnesothermic reaction to reduce CO2 to carbon nanotubes (a type of nanographite) of about 20 nm. However, after a single use, magnesium alloys permanently lose their ability to reduce CO2 again due to the formation of magnesium oxide. Alternatively, nanographite can be prepared by reducing CO2 gas using metallic calcium. However, besides the inability to regenerate calcium, this method involves a highly intense thermal reaction process (actual temperature >1000℃), which causes severe sintering between the nanographite and calcium carbonate, hindering the separation and mass production of nanographite. Summary of the Invention
[0005] To address the problems of long production cycles, high energy consumption, high graphitization temperatures, strict requirements on production equipment, difficulty in catalyst regeneration, and difficulty in product separation associated with nano-graphite, the present invention aims to provide a simple, low-cost, and continuously stable method for preparing high-quality nano-graphite. This method uses carbon dioxide as a carbon source, which is not only low-cost but also enables carbon fixation. Furthermore, the process is simple, has a short cycle, low energy consumption, low equipment requirements, and is easy to scale up for mass production.
[0006] To achieve the above-mentioned technical objectives, this invention provides a method for the catalytic conversion of carbon dioxide gas into nano-graphite. This method involves reducing and activating a nano-manganese ferrite catalyst, then catalytically converting carbon dioxide gas into nano-graphite at a temperature of 550–750°C. The chemical formula of the nano-manganese ferrite catalyst is Mn. X Fe 3-X O4, where the value of X ranges from 0.75 to 2.00.
[0007] The key to the method for catalytically converting carbon dioxide gas into nanographite provided by this invention lies in utilizing the high-temperature catalytic effect of manganese ferrite nanocatalysts. First, the manganese ferrite nanocatalyst is reduced using a reducing gas such as H2 to generate a large number of oxygen vacancies. These oxygen vacancies can capture carbon dioxide and simultaneously catalytically convert it into nanographite. Through reduction activation, the nano-manganese ferrite catalyst retains its spinel crystal structure while losing some lattice oxygen at the manganese ferrite surface. When CO2 gas flows through the oxygen vacancies on the surface of the manganese ferrite catalyst, the O=C=O... 2- Captured by oxygen vacancies, and aided by transition electrons provided during the electron transition from low-valence manganese and iron to high-valence manganese and iron in the octahedral center of the crystal lattice, the two C=O bonds break into elemental carbon. Furthermore, through the catalytic action of manganese ions in the tetrahedral center of the crystal lattice, carbon undergoes sp... 3 amorphous carbon (i.e., carbon of amorphous form) transforms into sp 2 Type (graphite). Extensive experiments also revealed that when the ratio of manganese to iron in the nano-manganese ferrite catalyst reaches a certain range, the reduced and activated nano-manganese ferrite catalyst within the temperature range of 550–750℃ can successfully catalyze the conversion of carbon dioxide into nano-graphite. This was unexpected. Research found that this is mainly based on the fact that manganese ions have a better catalytic performance than iron ions in breaking the C=O bond during the reduction of carbon dioxide to carbon. Simultaneously, Mn... 2+ In promoting sp 2 Carbon (i.e., amorphous carbon) to sp 3 Manganese (graphite) plays a crucial role in the catalytic conversion of carbon (graphite). When the temperature field reaches above 550℃, the catalytic fracture performance of manganese ions and Mn... 2+ The catalytic conversion effect is very active, which makes it possible to achieve a more obvious and stable conversion of carbon dioxide gas to nanographite by increasing the proportion of manganese in manganese ferrite and the thermal field temperature.
[0008] As a preferred embodiment, the manganese in the nano-manganese ferrite catalyst is in the valence state of Mn. 2+ Mn 3+ Mn 4+ At least one of them, the valence state of iron is Fe. 2+ Fe 3+ At least one of them.
[0009] As a preferred embodiment, at least one of H2 gas, CO gas, and CH4 gas is used as a reducing activator during the reduction activation process. Under appropriate reaction conditions, these reducing activators can bind oxygen in the manganese ferrite nanocatalyst lattice, thereby generating oxygen vacancies in the manganese ferrite nanocatalyst lattice. During the reduction activation process, H2 gas, CO gas, CH4 gas, etc., can be introduced in pure gas form, or diluted with an inert gas or nitrogen before being introduced.
[0010] As a preferred embodiment, the reduction activation conditions are: temperature of 250–350°C and time of 0.1–60 min. Under these preferred reduction activation conditions, the spinel crystal structure can be maintained even as some lattice oxygen is lost at the manganese ferrite interface. The reduction activation temperature is further preferably 295–345°C, and the reduction activation time is further preferably 1–35 min. If the reduction activation temperature is too low, the number of oxygen vacancies will be very small, resulting in low CO2 capture and conversion rates when the oxygen-deficient manganese ferrite comes into contact with CO2 gas. If the reduction activation temperature is too high, the spinel structure of the manganese ferrite will be destroyed, and Fe ions will be excessively reduced to metallic Fe, leading to complete catalyst deactivation.
[0011] As a preferred embodiment, the temperature during the catalytic conversion of carbon dioxide gas into nanographite is 600–700°C. If the temperature is too low, it will cause Mn… 2+ The activity of catalyzing the conversion of carbon into graphite decreases. If the temperature is too high, graphite will undergo a disproportionation reaction with CO2 to generate new CO greenhouse gas.
[0012] In a preferred embodiment, during the catalytic conversion of carbon dioxide gas into nano-graphite, the flow rate of carbon dioxide gas is 1–200 mL / min, and the time is 0.1–60 min. The flow rate of carbon dioxide gas affects the generation rate of nano-graphite. Too high a flow rate will cause the nano-manganese ferrite catalyst powder to be compacted, leading to a decrease in the mass transfer efficiency of the gas-solid reaction and a reduction in the graphite generation rate. While a too slow flow rate can ensure the smooth generation of graphitic carbon, maintaining the thermal field temperature for a prolonged period results in meaningless energy consumption. Too short a carbon dioxide gas introduction time will prevent the nano-manganese ferrite catalyst from fully exerting its catalytic effect, resulting in a low carbon conversion rate and graphitization degree; conversely, if the carbon dioxide gas introduction time is long, the gas-solid reaction may have ended, but the continued introduction of CO2 gas will result in waste of CO2 gas. Carbon dioxide gas can be introduced in pure gas form, or diluted with an inert gas or nitrogen before introduction. The flow rate of carbon dioxide gas is further preferably 5–100 mL / min. The introduction time of carbon dioxide gas is further preferably 5–45 min.
[0013] After the reaction of catalytic carbon dioxide gas to nano-graphite is completed, the nano-manganese ferrite catalyst is soaked in dilute acid, and then the nano-manganese ferrite catalyst is adsorbed by a strong magnet to achieve solid-liquid separation and catalyst recovery. The carbon product obtained after the liquid is centrifuged at high speed and vacuum dried is nano-graphite.
[0014] The present invention provides a method for the catalytic conversion of carbon dioxide gas into nano-graphite, comprising the following specific steps:
[0015] (1) Analytical grade manganese oxide (MnO2 / Mn2O3 / Mn3O4) and iron oxide (Fe2O3 / Fe3O4) were weighed and thoroughly mixed according to the molar ratio of Mn to Fe of 0.75:2.25~2.00:1.00. After blistering, the mixture was heated to 1200~1500℃ at a heating rate of 1~20℃ / min and held at that temperature for 1~12h. After high-temperature calcination, the mixture was rapidly cooled. The calcined blister was wet-milled to nanoscale size (1~200nm) using a nano-sand mill. After solid-liquid separation, the mixture was vacuum dried to obtain nano-manganese ferrite catalyst powder.
[0016] (2) Add nano-manganese ferrite catalyst powder into a fixed-bed reactor, introduce inert gas at a rate of 10-1000 mL / min, and adjust the temperature of the fixed-bed reactor to 250-350℃.
[0017] (3) H2 gas with a flow rate of 1 to 500 mL / min is introduced into the fixed bed reactor for a time of 0.1 to 60 min;
[0018] (4) Switch the gas introduced to an inert gas with a flow rate of 10 to 1000 mL / min, and adjust the temperature of the fixed bed reactor to 550 to 750℃;
[0019] (5) The gas introduced is switched to CO2 gas with a flow rate of 1 to 200 mL / min and the introduction time is 0.1 to 60 min;
[0020] (6) Switch the gas introduced to an inert gas with a flow rate of 10-1000 mL / min and cool the fixed bed reactor to room temperature;
[0021] (7) Soak the nano-manganese ferrite catalyst in dilute hydrochloric acid with a volume concentration of 0.1 to 1M for 0.1 to 12 hours. Use a strong magnet to adsorb manganese ferrite onto the inner wall of the container to achieve solid-liquid separation and catalyst recovery. The carbon product obtained after the liquid is centrifuged at high speed and vacuum dried is nano-graphite.
[0022] The nano-manganese ferrite catalyst used in this invention has a large specific surface area, which can promote more contact and reaction with CO2 gas, thereby producing more nano-graphite. If the particle size of the nano-manganese ferrite catalyst is too large (>200 nm), it will lead to a significant reduction in catalytic performance and nano-graphite yield. The spinel lattice of manganese ferrite has oxygen ions in a close-packed arrangement, surrounding manganese and iron ions in tetrahedral and octahedral packing. Among them, a larger number of Mn atoms are distributed at the octahedral centers. 2+ and Fe 2+ This ensures that more CO2 gas is reduced to C. More Mn is distributed in the tetrahedral center. 2+ This ensures the conversion of amorphous carbon into graphite.
[0023] Compared with existing technologies, the beneficial technical effects of the present invention are as follows:
[0024] 1) The process for preparing nano-graphite in this invention is simple, has a short cycle, low energy consumption, low equipment requirements, and is easy to mass-produce.
[0025] 2) The raw material for preparing nano-graphite in this invention is carbon dioxide, which is widely available. For example, waste CO2 gas captured by factories or CO2 gas captured directly from the air can be used. The cost is low, and carbon can be effectively fixed and converted into high-value-added nano-graphite, enabling sustainable and stable production.
[0026] 3) The nano-manganese ferrite catalyst used in the preparation of nano-graphite in this invention is low in cost. Manganese and iron are the cheapest metals in the periodic table. At the same time, manganese ferrite also has the characteristics of strong magnetism, acid resistance and high temperature resistance, and is easy to regenerate and recycle.
[0027] 4) The nano-graphite prepared by this invention has a high degree of graphitization and a particle size of less than 120 nm, resulting in good quality. Attached Figure Description
[0028] Figure 1 The images show the laser particle size distribution (a), XRD patterns (b) before and after nano-sand milling, SEM images (c) of the nano-manganese ferrite catalyst after nano-sand milling, and specific surface area results (d) of the manganese ferrite catalyst used in Example 1 during the nano-sand milling process.
[0029] Figure 2 This is the Raman spectrum of the nanographite prepared in Example 1.
[0030] Figure 3 This is a transmission electron microscope (TEM) image of the nanographite prepared in Example 1.
[0031] Figure 4 This is the Raman spectrum of the nano-carbon prepared in Comparative Example 1. Detailed Implementation
[0032] The following specific embodiments are intended to further illustrate the content of the present invention, rather than to limit the scope of protection of the claims.
[0033] Example 1
[0034] Analytical grade Mn₂O₃ and Fe₂O₃ were weighed and thoroughly mixed according to a molar ratio of Mn:Fe of 0.882:2.118. After calcination, the mixture was heated to 1400℃ at a heating rate of 10℃ / min and held at that temperature for 8 hours. Following high-temperature calcination, the mixture was rapidly cooled. The calcined agglomerates were then wet-milled to nanoscale (50nm) using a nano-milling mill. After solid-liquid separation, the mixture was vacuum-dried to obtain nano-manganese ferrite catalyst powder. 1g of this manganese ferrite nano-catalyst (chemical formula Mn₂O₃) was...0.882 Fe 2.118 O4 was added to a fixed-bed reactor, and Ar gas was introduced at a rate of 50 mL / min. The reactor was then heated to 335 °C. Next, the gas flow was switched to a 10% H2 / Ar mixture at a rate of 100 mL / min for 30 min. Afterward, the gas flow was switched to Ar gas at a rate of 20 mL / min, and the reactor was heated to 680 °C. Then, the gas flow was switched to a 35% CO2 / He mixture at a rate of 50 mL / min for 35 min. Finally, the gas flow was switched back to Ar gas at a rate of 30 mL / min, and the reactor was cooled to room temperature. The reacted manganese ferrite catalyst was soaked in 0.5 M dilute hydrochloric acid for 2 h, and then the catalyst was adsorbed onto the outer wall of the container using a strong magnet to achieve solid-liquid separation. Nano-graphite powder was obtained by centrifugation and vacuum drying.
[0035] The Raman spectrum of the nano-graphite powder prepared in this embodiment is as follows: Figure 1 As shown, by Figure 2 As can be seen, the Raman results show only the G peak and no D peak, indicating that the synthesized nanographite has a very high degree of crystallinity and contains no amorphous carbon. The transmission electron microscope (TEM) image of the nanographite powder prepared in this example is shown below. Figure 3 As shown in the figure, the nanographite exhibits a distinct layered structure, resembling graphite spheres formed by stacked layers. On a 50nm scale, the particle size of the nanographite is approximately 30–100nm. This indicates that the nanographite prepared in this embodiment is of very high quality.
[0036] Example 2
[0037] Analytical grade MnO2 and Fe2O3 were weighed and thoroughly mixed according to a molar ratio of Mn:Fe of 1.293:1.707. After calcination, the mixture was heated to 1250℃ at a heating rate of 5℃ / min and held at that temperature for 3 hours. Following high-temperature calcination, the mixture was rapidly cooled. The calcined agglomerates were then wet-milled to nanoscale size (68nm) using a nano-milling mill. After solid-liquid separation, the mixture was vacuum-dried to obtain nano-manganese ferrite catalyst powder. 3g of this manganese ferrite nano-catalyst (chemical formula MnO2:Fe2O3) was... 1.293 Fe 1.707O4 was added to a fixed-bed reactor, and Ar gas was introduced at a rate of 200 mL / min. The reactor was then heated to 320 °C. Next, the gas flow was switched to a 30% H2 / Ar mixture at a rate of 50 mL / min for 35 min. Afterward, the gas flow was switched back to Ar gas at a rate of 50 mL / min, and the reactor was heated to 600 °C. Then, the gas flow was switched to a 50% CO2 / Ar mixture at a rate of 50 mL / min for 35 min. Finally, the gas flow was switched to N2 gas at a rate of 100 mL / min, and the reactor was cooled to room temperature. The reacted manganese ferrite catalyst was soaked in 1.0 M dilute hydrochloric acid for 0.5 h, and then the catalyst was adsorbed onto the outer wall of the container using a strong magnet to achieve solid-liquid separation. Nano-graphite powder was obtained by centrifugation and vacuum drying.
[0038] The nano-graphite prepared in this embodiment has a very high degree of crystallization, with a particle size of 20-95 nm and a very high quality.
[0039] Example 3
[0040] Analytical grade Mn3O4 and Fe3O4 were weighed and thoroughly mixed according to a molar ratio of Mn:Fe of 1.581:1.419. After calcination, the mixture was heated to 1200℃ at a heating rate of 20℃ / min and held at that temperature for 3 hours. Following high-temperature calcination, the mixture was rapidly cooled. The calcined agglomerates were then wet-milled to nanoscale (100nm) using a nano-milling mill. After solid-liquid separation, the mixture was vacuum-dried to obtain nano-manganese ferrite catalyst powder. 0.5g of this manganese ferrite nanocatalyst (chemical formula Mn3O4) was then... 1.581 Fe 1.419 O4 was added to a fixed-bed reactor, and Ar gas was introduced at a rate of 10 mL / min. The reactor was then heated to 345 °C. Next, the gas flow was switched to a 50% H2 / Ar mixture at a rate of 10 mL / min for 10 min. Afterward, He gas was introduced at a rate of 10 mL / min, and the reactor was heated to 655 °C. A 20% CO2 / Ar mixture was then introduced at a rate of 10 mL / min for 15 min. Finally, N2 gas was introduced at a rate of 20 mL / min, and the reactor was cooled to room temperature. The reacted manganese ferrite catalyst was soaked in 0.3 M dilute hydrochloric acid for 3 h. Then, the manganese ferrite catalyst was adsorbed onto the outer wall of the container using a strong magnet to achieve solid-liquid separation. Nano-graphite powder was obtained by centrifugation and vacuum drying.
[0041] The nano-graphite prepared in this embodiment has a very high degree of crystallization, with a particle size of 10-75 nm and a very high quality.
[0042] Example 4
[0043] Analytical grade MnO2 and Fe3O4 were weighed and thoroughly mixed according to a Mn:Fe molar ratio of 1.917:1.083. After calcination, the mixture was heated to 1350℃ at a heating rate of 10℃ / min and held at that temperature for 5 hours. Following high-temperature calcination, the mixture was rapidly cooled. The calcined agglomerates were wet-milled to nanoscale size (158nm) using a nano-milling mill. After solid-liquid separation, the mixture was vacuum-dried to obtain nano-manganese ferrite catalyst powder. 30g of this manganese ferrite nano-catalyst (chemical formula MnO2:Fe3O4) was then... 1.917 Fe 1.083 O4 was added to a fixed-bed reactor, and N2 gas was introduced at a rate of 500 mL / min. The reactor was then heated to 300 °C. Next, the gas flow was switched to a 40% H2 / N2 mixture at a rate of 300 mL / min for 20 min. Afterward, the gas flow was switched to N2 at a rate of 100 mL / min, and the reactor was heated to 580 °C. Then, the gas flow was switched to a 20% CO2 / N2 mixture at a rate of 100 mL / min for 15 min. Finally, the gas flow was switched to N2 at a rate of 50 mL / min, and the reactor was cooled to room temperature. The reacted manganese ferrite catalyst was soaked in 0.9 M dilute hydrochloric acid for 1 h, and then the catalyst was adsorbed onto the outer wall of the container using a strong magnet to achieve solid-liquid separation. Nano-graphite powder was obtained by centrifugation and vacuum drying.
[0044] The nano-graphite prepared in this embodiment has a very high degree of crystallization, with a particle size of 30-110 nm and a very high quality.
[0045] Comparative Example 1
[0046] In this comparative example, the X value of manganese ferrite is not within the range protected by this invention.
[0047] Analytical grade Mn₂O₃ and Fe₂O₃ were weighed and thoroughly mixed according to a molar ratio of Mn:Fe of 0.40:2.60. After calcination, the mixture was heated to 1400℃ at a heating rate of 10℃ / min and held at that temperature for 8 hours. Following high-temperature calcination, the mixture was rapidly cooled. The calcined agglomerates were then wet-milled to nanoscale (50nm) using a nano-milling mill. After solid-liquid separation, the mixture was vacuum-dried to obtain nano-manganese ferrite catalyst powder. 1g of this manganese ferrite nano-catalyst (chemical formula Mn₂O₃) was... 0.40 Fe 2.60 O4) is added to the fixed-bed reactor. The gas introduction method, gas flow rate, gas concentration, gas introduction time, and temperature settings of the fixed-bed reactor are exactly the same as in Example 1.
[0048] The Raman spectra of the carbon powder prepared in this comparative example are as follows: Figure 4 As shown in the figure. Peak separation analysis reveals that the graphitization degree I of the calcium-carbon product is... G / ID It has a graphitization rate of only 9.81%, indicating a low degree of graphitization and poor quality.
[0049] Comparative Example 2
[0050] In this comparative embodiment, the CO2 gas introduction time of manganese ferrite is outside the scope protected by this invention.
[0051] Analytical grade MnO2 and Fe2O3 were weighed and thoroughly mixed according to a molar ratio of Mn:Fe of 1.20:1.80. After calcination, the mixture was heated to 1250℃ at a heating rate of 5℃ / min and held at that temperature for 3 hours. After high-temperature calcination, the mixture was rapidly cooled. The calcined agglomerates were wet-milled to nanoscale size (68nm) using a nano-milling mill. After solid-liquid separation, the mixture was vacuum-dried to obtain nano-manganese ferrite catalyst powder. 1g of this manganese ferrite nanocatalyst (chemical formula MnO2:Fe2O3) was... 1.20 Fe 1.80 O4) was added to the fixed-bed reactor. Except for the CO2 introduction time of 1 minute, all other conditions, including the gas introduction method, gas flow rate, gas concentration, gas introduction time, and temperature setting of the fixed-bed reactor, were exactly the same as in Example 2.
[0052] The carbon powder prepared in this comparative example has a low degree of graphitization and poor quality.
Claims
1. A method for the catalytic conversion of carbon dioxide gas into nano-graphite, characterized in that: The nano-manganese ferrite catalyst was reduced and activated, and then catalyzed to convert carbon dioxide gas into nano-graphite at a temperature of 600-700℃; the chemical formula of the nano-manganese ferrite catalyst is Mn. X Fe 3-X O4, where the value of X ranges from 0.75 to 2.
00.
2. The method for catalytically converting carbon dioxide gas into nano-graphite according to claim 1, characterized in that: The valence state of manganese in the nano-manganese ferrite catalyst is Mn. 2+ Mn 3+ Mn 4+ At least one of them, the valence state of iron is Fe. 2+ Fe 3+ At least one of them.
3. The method for catalytically converting carbon dioxide gas into nano-graphite according to claim 1, characterized in that: In the reduction and activation process, at least one of H2 gas, CO gas, and CH4 gas is used as the reduction and activating agent.
4. A method for catalytically converting carbon dioxide gas into nano-graphite according to claim 1 or 3, characterized in that: The conditions for reduction and activation are: temperature of 250~350℃ and time of 0.1~60min.
5. The method for catalytically converting carbon dioxide gas into nano-graphite according to claim 1, characterized in that: In the process of catalytically converting carbon dioxide gas into nano-graphite, the flow rate of carbon dioxide gas is 1~200 mL / min, and the time is 0.1~60 min.
Citation Information
Patent Citations
High temperature graphitization method for nano carbon material
CN103435032A
Electrochemical method for converting amorphous carbon into graphite
CN103510103A
Method for preparing high thermal conductivity graphite through catalytic graphitization
CN106495147A
Method for preparing nanographene sheet
CN106498468A
Preparation method of nano graphite sheets
CN106744914A